2007
DOI: 10.1902/jop.2007.060271
|View full text |Cite
|
Sign up to set email alerts
|

Two Human Hydroxyapatite‐Coated Dental Implants Retrieved After a 14‐Year Loading Period: A Histologic and Histomorphometric Case Report

Abstract: No acute or chronic inflammatory cell infiltrate was present in the peri-implant tissues. No signs of coating infection, fatigue, or failure were observed in two specimens. The HA coating may not be susceptible to degradation or dissolution under long-term function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…HA coating as a system of fixation of hip implants was found to work well in the short to medium term (eight years [505], 10 to 15.5 years [506], 15 years [507], 16 years [508], 17 years [509], 19 years [510] and 15 to 21 years [511]). Similar data for HA-coated dental implants are also available [512,513]. Even longer-term clinical results are awaited with great interest.…”
Section: Biomedical Applicationsmentioning
confidence: 88%
“…HA coating as a system of fixation of hip implants was found to work well in the short to medium term (eight years [505], 10 to 15.5 years [506], 15 years [507], 16 years [508], 17 years [509], 19 years [510] and 15 to 21 years [511]). Similar data for HA-coated dental implants are also available [512,513]. Even longer-term clinical results are awaited with great interest.…”
Section: Biomedical Applicationsmentioning
confidence: 88%
“…Separation of the HA coating from the titanium surface has been documented on HA-coated blade-form implants (Takeshita et al 1996) and delamination of the HA coatings after 16 weeks has been reported in implants placed in rabbits tibias (Lin et al 1998). In contrast, human studies with HA-coated root-form dental implants retrieved after up to 14 years in function have reported that HA coatings were in contact with mature bone and that the HA coating was not susceptible to degradation or dissolution under long-term function (Proussaefs et al 2001;Lezzi et al 2007;Coelho et al 2010). It is possible that the design of LTPD implants as well as the clinical technique used in their placement may play an important role in the performance of the HA-coated implants documented in this study.…”
Section: The Effect Of An Ha Coatingmentioning
confidence: 99%
“…HA coating as a system of fixation of hip implants was found to work well in the short to medium term ( [567]. Similar data for HA-coated dental implants are also available [568,569]. Even longer-term clinical results are awaited with a great interest.…”
Section: Coatingsmentioning
confidence: 84%